110k views
0 votes
Find the distance between the given points (2 √ 3 , -√ 13) and (6 √ 3 , √ 13)

1 Answer

4 votes

Find the distance between the given points (2 √ 3 , -√ 13) and (6 √ 3 , √ 13)

Remember that

The formula to calculate the distance between two points is equal to


d=\sqrt[]{(y2-y1)^2+(x2-x1)^2}

substitute the given points in the formula


d=\sqrt[]{(\sqrt[]{13}+\sqrt[]{13})^2+(6\sqrt[]{3}-2\sqrt[]{3})^2}
d=\sqrt[]{(2\sqrt[]{13})^2+(4\sqrt[]{3})^2}
\begin{gathered} d=\sqrt[]{52^{}+48^{}} \\ d=\sqrt[]{100} \\ d=10\text{ units} \end{gathered}

User Andreasdr
by
5.9k points